Cycling training for endothelial dysfunction correction and atherosclerotic risk factor modification in young males (data from Tomsk City university students’ survey) - G. B. Krivulina; V. N. Kim; R. S. Karpov; V. M. Shevelev (Кардиоваскулярная терапия и профилактика, 2006)
Aim. To assess physical training (PT) effect on NO-dependent vascular and autonomous tonus disturbances in male students with atherosclerosis risk factors (ARF) and endothelial dysfunction (ED), as well as to develop the optimal PT protocol. Material and methods. In 90 healthy males, aged under 25 years, with ARF and ED, PT sessions were held 3 times per week: 30 individuals were training for 1 month, 30 – for 2 months, and 30 – for 3 months. At baseline and after PT course, lipid profile, blood pressure, physical stress tolerance, double product at rest and in physical stress were measured. Cardiointervalography and brachial artery Doppler angiography were performed at rest, as well as in hyperemia and hyperventilation tests. Control groups I and II included 30 students each; the participants with or without ARF did not underwent any PT course. Results. Endothelial and autonomous dysfunction limited oxygen-transporting system and oxygen-recipient tissue functional potential, decreased energy-producing reserve and aerobic capacity in students with ARF and ED. Onemonth PT was not enough for ED normalization, and three-month PT demonstrated proatherogenic effects.  Conclusion. Two-month PT protocol for ED correction and ARF modification increased primary prevention effectiveness in young students from cardiovascular risk groups.